Primary social and emotional aspects of learning (SEAL) small group interventions: a qualitative study of factors affecting implementation and the role of Local Authority support - Neil Humphrey; Ann Lendrum; Michael Wigelsworth; Afroditi Kalambouka (International Journal of Emotional Education, 2009)
The aims of the current study were to examine the factors affecting implementation of social and emotional aspects of learning (SEAL) small group interventions in primary schools and to explore the role of support from Local Authorities (LAs) in the implementation process. Telephone interviews were conducted with lead SEAL staff in 12 LAs across England as part of a larger national evaluation of this educational initiative. Data were transcribed and subjected to qualitative content analysis. Subsequently, a tentative model was developed to document the relationship between the nature of support provided by LAs (e.g. training events, developing/providing additional materials), factors affecting implementation at school level (e.g. school readiness, the profile of SEAL) and perceived barriers to success (e.g. misconceptions about the purpose of small group interventions). These findings are discussed in relation to the existing literature on the implementation of social-emotional initiatives and interventions in education.